An Experience of Jigsaw as a New Educational Method in Dentistry - Atekeh Movaghari pour; Mostafa Sadeghi; Foad Iranmanesh; Fatemeh Sadat Emami; Faezeh Esmaeili Ranjbar (Journal of Mashhad Dental School)
Background: Considering that simply relying on conventional education methods no longer suffices, educational systems have attempted to employ novel and active learning methods in their curriculum.  This study aimed to compare the effectiveness of jigsaw versus lecture-based learning in undergraduate dental students.Method and Materials: A total of 31 undergraduate dental students attending Rafsanjan Dental School, Rafsanjan, Iran were recruited for this study. Students had all taken a course on Oral Medicine and we decided to evaluate their knowledge regarding pigmented oral lesions. Participants were randomly divided to two groups. Each group received a teaching session, one using the Jigsaw method (experimental group) and the other one using a lecture-based approach (control group). Pre- and post-intervention tests were conducted to evaluate knowledge acquisition. Three months after training, all students had to take their final exam and their obtained scores were also recorded and compared. The complete test scores was a maximum of 20. Independent and paired-samples T-tests were used for statistical analysis. P<0.05 was considered statistically significant. Results: The experimental and control group obtained a mean pre-intervention score of 6.50±1.16 and 5.80±1.78, respectively (P=0.210). The post-intervention test scores were 9.06±3.24 in the Jigsaw group and 9.73± 2.71 in the lecture group (P=0.538). Both Jigsaw and lecture-based methods significantly improved students’ knowledge regarding pigmented oral lesions, with mean scores demonstrating a significant difference pre- and post-intervention and three months later during the final exam (P<0.001 for all). However, Independent samples T-test revealed that the two groups were not significantly different in terms of the mean scores or the amount of increase in scores at any evaluation interval (P>0.05 for all).Conclusion: After a short- and long-term evaluation, using the Jigsaw method for teaching undergraduate dental students about pigmented oral lesions yielded comparable results to the traditional lecture-based learning method.